1989
DOI: 10.1046/j.1537-2995.1989.29589284140.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of white cells from platelet concentrates with a new adsorption filter

Abstract: Removal of white cells (WBCs) from platelets may reduce alloimmunization to WBC antigens, prevent febrile reactions, and improve platelet increments in multiply transfused patients receiving HLA-matched platelets. A new surface-modified fibrous polyester filter was evaluated; it requires no special processing of pooled platelet concentrates and can be used at the patient's bedside. The studies were designed to measure WBC removal, platelet function, in vitro platelet recovery, and in vivo platelet survival. WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(27 citation statements)
references
References 13 publications
2
23
1
1
Order By: Relevance
“…In addition, another important structural component of the platelet membrane, glycoprotein IlbIlla, was not modified by filtration. This further supports the conclusions of previous studies indicating that filtered platelets retain hemostatic effectiveness [9,21] and normal survival [15,17], The wide range of pre-and postfiltration values shown by GMP 140 could suggest that a proportion of our platelets were already activated before filtration, which confirms other data indicating that a slight level of activation may exist in some PC soon after preparation [22]. However, GMP 140 expression before filtration was lower than that found in platelets stored in polyolefin for 5 days [Bertolini et al, unpubl.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, another important structural component of the platelet membrane, glycoprotein IlbIlla, was not modified by filtration. This further supports the conclusions of previous studies indicating that filtered platelets retain hemostatic effectiveness [9,21] and normal survival [15,17], The wide range of pre-and postfiltration values shown by GMP 140 could suggest that a proportion of our platelets were already activated before filtration, which confirms other data indicating that a slight level of activation may exist in some PC soon after preparation [22]. However, GMP 140 expression before filtration was lower than that found in platelets stored in polyolefin for 5 days [Bertolini et al, unpubl.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study indicate that leukocyte removal and platelet recovery are satisfactory with all three filters examined, although statistically significant variations in performance were found. Differences in platelet recovery and leukocyte con tamination among this study, our previous investigation [9] and other reports [15][16][17][18] are probably due to technical factors including the number of PC in the filtered pool, the method of residual leukocyte count, and the rinsing maneu ver which was performed by some investigators with vari-In summary, leukocyte removal of Sepacell PL-10A was higher than that of Pall PL100 and Imugard IG 500; this was associated to a significantly higher platelet loss than that with Imugard. Filtration through the three filters examined did not determine significant modifications of platelet membrane glycoprotein Ilb-IIIa and of other constituents related to platelet activation, in vivo recovery and survival.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Recently, a sterile connection device has become available, and storage of pooled and/or fil tered platelet concentrates appears to be practicable. Al though a number of investigators reported in vitro charac teristics and in vivo effectiveness of filtered PC evaluated soon after filtration [2][3][4][5], studies on the feasibility of PC storage after filtration are scanty. Instead of using the traditional method of PC preparation from platelet-rich Materials and Methods bound fibrinogen, a kind gift of Dr. Budzynski (Philadelphia, Pa., USA).…”
Section: Introductionmentioning
confidence: 99%
“…Filters to remove leukocytes from erythrocyte trans fusions have been available for more than 10 years, but only recently have filters become available that could re move white cells from platelet suspensions without con siderable platelet loss [9][10][11]. A point of concern is wheth er filtration causes damage to platelets, as during the fil tration procedure platelets are exposed to foreign surfaces which may cause platelet activation with release of in ternal constituents, compromising clinical efficacy of the transfused platelets.…”
Section: Introductionmentioning
confidence: 99%